INTEGRATION OF REALISTIC MATHEMATICS EDUCATION (RME) APPROACH IN MATHEMATICS LEARNING TO IMPROVE CRITICAL THINKING OF ELEMENTARY SCHOOL STUDENTS - Eko Pujianto (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2025)
This study aims to describe the implementation of the Realistic Mathematics Education (RME) approach in mathematics learning and its impact on improving the critical thinking skills of elementary school students. The method used is descriptive qualitative with data collection techniques through observation, interviews, and documentation. The research subjects consisted of teachers and grade V students in one of the elementary schools in Medan City. The results of the study show that the RME approach is implemented through the stages of presenting contextual problems, mathematical modeling, and reflection. This approach encourages students' active involvement in the thought process and group discussions. The consistent implementation of RME results in improvements in students' critical thinking indicators, such as the ability to identify problems, provide logical reasons, evaluate solutions, and draw conclusions. In addition, students show higher enthusiasm and motivation to learn because the learning material is considered more relevant to their lives. These findings suggest that the integration of the RME approach can be an effective strategy in developing students' critical thinking skills early on, as well as supporting meaningful learning in accordance with the principles of a competency-based and character-based curriculum.